THE INFLUENCE OF SCHOOL CULTURE AND TEACHERS' COMMITMENT ON THE PEDAGOGICAL COMPETENCIES OF ELEMENTARY TEACHERS - ESHAS, Galtania Amoria (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2023)
This research aims to investigate the influence of School Culture (X1) and Teacher Commitment (X2) on the Pedagogical Competence (Y) of Elementary School Teachers in Sukmajaya District, Depok City. This research uses an associative quantitative approach and hypothesis testing using the path analysis method, while the data collection technique uses questionnaires, with a sample of 98 teachers from a population of 130 elementary school teachers in the Sukmajaya sub-district, Depok City. Based on the results of hypothesis testing from the research discussion, several conclusions can be put forward as follows: a) Statistical results show that there is a partially positive and significant influence between School Culture and Pedagogical Competence (t count = 16.455, sig = 0.000 < 0.05), b) Statistical results show that there is a partially positive and significant influence between Teacher Commitment on Pedagogical Competence (tcount = 47.251, sig = 0.000 < 0.05), c) Statistical results show that there is a partially positive and significant influence between School Culture on Teacher Commitment (tcount = 11.324, sig = 0.000 < 0.05). Thus, from the results of this research and discussion, it can be concluded that School Culture, Teacher Commitment, and Pedagogical Competence are interrelated and influence each other. Improving School Culture and Teacher Commitment can make a positive contribution in improving Pedagogical Competence in the educational environment. This research aims to investigate the influence of School Culture (X1) and Commitment.